Development Of LED-Based Props on Planetary Type Starter Motor Maintenance Competency in Vocational Schools - Jamal, Ahmad Syarifudin; Hadromi, Hadromi (Universitas Negeri Semarang, 2021)
This study aims to develop and evaluate the feasibility level of a planetary type starter motor maintenance aids at the Light Vehicle Engineering’s expertise program in the Vocational High Schools (VHS). The research was conducted in Semarang Vocational High Schools. The study uses of development models consist of 4 stage (Four D) namely: Define, Design, Develop and Disseminate. This feasibility of props development results tested on media feasibility tests, material feasibility tests, test of improvement of learning outcomes between students whose learning is applied props with students who are not applied props and student responses to developed props. Analysis of media and material feasibility data using descriptive techniques, analysis of improved student learning outcomes using t-test tests that previously conducted normality tests, homogeneity tests. Based on the results of the study, props were declared eligible to be applied in vocational schools with an acquisition of 94.44% for media experts and 96.25% for material experts. Improved student learning outcomes from t-test results. The analysis of students' responses to props obtained by 87.60% was very well categorized.